O-GlcNAcylation of FOXK1 co-opts BAP1 to orchestrate the E2F pathway and promotes oncogenesis - Oumaima Ahmed; Louis Masclef; Nicholas Iannantuono; Jessica Gagnon; Mila Gushul-Leclaire; Karine Boulay; Benjamin Estavoyer; Mohamed Echbicheb; Kalidou Ali Boubacar; Marty Poy; Amina Boubekeur; Saad Menggad; et al. (Nature Communications)
Abstract The E2F transcription factors constitute a core transcriptional network that governs cell division and oncogenesis in multi-cellular organisms, although their molecular mechanisms remain incompletely understood. Here, we show that elevated expression of the transcription factor FOXK1 promotes transcription of E2F target genes and cellular transformation. High expression of FOXK1 in patient tumors is also strongly correlated with E2F gene expression. Mechanistically, we demonstrate that FOXK1 is O-GlcNAcylated, and loss of this modification impairs FOXK1 ability to promote cell proliferation and tumor growth. We also show that expression of FOXK1 O-GlcNAcylation-defective mutants results in reduced recruitment of the H2AK119 deubiquitinase and tumor suppressor BAP1 to E2F target genes. This event is associated with a transcriptional repressive chromatin environment and reduced cell proliferation. Our results define an essential role of FOXK1 O-GlcNAcylation in co-opting the tumor suppressor BAP1 to promote cancer cell progression through orchestration of the E2F pathway.